On the microstructure and properties of an advanced cemented carbide system processed by selective laser melting - Li, Chen-Wei; Chang, Kai-Chun; Yeh, An-Chou (Journal of alloys and compounds, 2019)
This article presents a study on the influence of selective laser melting (SLM) process on microstructure and property of a cemented carbide system containing high entropy alloy. Analysis along the building direction indicated variation of chemical composition and microstructure, and this was influenced by two effects, firstly the dilution effect due to elemental diffusion from the baseplate and secondly the elements evaporation caused by high-power laser. At the lower half of the specimen, high fraction of η-carbide formed near the level of baseplate, and there were chemical gradients of major binder elements along the building direction. At the upper half of the specimen, there were relatively less variation in chemical composition and more homogeneously distributed phases including WC, W2C, η-carbide and FCC metal binder. The hardness of the lower half specimen varied from 711.7 HV1 (bottom of the specimen) to 1178.6 HV1 at 1 mm height. For the upper half of the specimen, hardness values could range from 1306.8 HV1 to 1413.4 HV1 and fracture toughness varied from 9.74 MPa m1/2 to 13.29 MPa m1/2. •A complex cemented carbide system was subjected to selective laser melting process.•The cemented carbide system contains a high entropy alloy.•Composition and microstructure of the cemented carbide were heterogeneous.•Dilution effect, evaporation, and laser scanning tracks could affect the built.•Hardness and toughness varied due to variation in composition and microstructure.